HUBUNGAN DDIMER GULA DARAH DAN ASAM URAT DENGAN VOLUME INFARK DAN KELUARAN PADA STROKE ISKEMIK - Maria Thessarina Sitepu, Darulkutni Nasution, Cut Aria Arina (Neurona Majalah Kedokteran Neuro Sains, 2014)
INTRODUCTION THERE ARE SOME FACTORS THAT CAN INFLUENCE THE OUTCOME OF ACUTE ISCHEMIC STROKE SUCH AS DDIMER LEVEL BLOOD GLUCOSE LEVEL AND URIC ACID LEVEL IT IS STILL CONTROVERSIAL WHETHER THESE FACTORS ACT AS A RISK FACTOR OR PROTECTIVE FACTOR